Analysis of the correlation between the serum triglyceride glucose index and the risk of death in patients on maintenance hemodialysis: a retrospective cohort study - Xiaokeng Chi; Shuxin Chen; Zhe Huang; Rong Zhou; Zhicheng Su; Qiujun Mai; Yilin Xu; Jianxin Wan (PeerJ)
Background Patients with end-stage renal disease (ESRD) have increased insulin resistance (IR). The triglyceride glucose (TyG) index is a marker of IR and is associated with the prognosis of patients on maintenance hemodialysis (MHD). The aim of this study was to examine the relationship between the TyG index and the risk of death in patients on MHD. Methods In a retrospective cohort analysis of 368 patients with MHD over an 11-year period from July 1, 2012, to June 30, 2023, the TyG index and other baseline characteristics were measured at the beginning of MHD treatment. A regression model was used to evaluate the correlation between the TyG index and all-cause mortality or cardiovascular mortality in patients on MHD. Results The TyG index was associated with all-cause mortality and cardiovascular mortality in MHD patients (P = 0.002 & P = 0.015). After adjusting for various confounding factors, the TyG index remained an independent predictor of all-cause mortality and cardiovascular mortality in MHD patients (P < 0.001 & P = 0.044). Compared with MHD patients with low TyG index levels, the risk of all-cause mortality and cardiovascular mortality in MHD patients with high TyG index levels increased by 1.790 and 1.735 times, respectively (P = 0.006 & P = 0.022). The predictive time-AUC values of the TyG index for all-cause and cardiovascular death in MHD patients were between 0.698 to 0.819. Conclusion The baseline TyG index may be an independent predictor of all-cause mortality and cardiovascular mortality in MHD patients.